Mitochondrial dysfunction in epilepsy - Folbergrová, Jaroslava; Kunz, Wolfram S (Mitochondrion, 2012)
Mitochondrial dysfunction has been identified as one potential cause of epileptic seizures. Impaired mitochondrial function has been reported for the seizure focus of patients with temporal lobe epilepsy and Ammon's horn sclerosis and of adult and immature animal models of epilepsy. Since mitochondrial oxidative phosphorylation provides the major source of ATP in neurons and mitochondria participate in cellular Ca(2+) homeostasis and generation of reactive oxygen species, their dysfunction strongly affects neuronal excitability and synaptic transmission. Therefore, mitochondrial dysfunction is proposed to be highly relevant for seizure generation. Additionally, mitochondrial dysfunction is known to trigger neuronal cell death, which is a prominent feature of therapy-resistant epilepsy. For this reason mitochondria have to be considered as promising targets for neuroprotective strategies in epilepsy.
Keywords: energetický metabolismus; homeostáza; modely nemocí na zvířatech; Mitochondria; Calcium; reaktivní formy kyslíku; vápník; Homeostasis; neurony; epilepsie; Reactive Oxygen Species; Animals; lidé; Energy Metabolism; Humans; zvířata; Neurons; Disease Models, Animal; Epilepsy; mitochondrie